2019
DOI: 10.1007/s00394-019-01925-6
|View full text |Cite
|
Sign up to set email alerts
|

Allyl isothiocyanate regulates lysine acetylation and methylation marks in an experimental model of malignant melanoma

Abstract: Objective(s) Isothiocyanates (ITCs) are biologically active plant secondary metabolites capable of mediating various biological effects including modulation of the epigenome. Our aim was to characterize the effect of allyl isothiocyanate (AITC) on lysine acetylation and methylation marks as a potential epigenetic-induced anti-melanoma strategy. Methods Our malignant melanoma model consisted of (1) human (A375) and murine (B16-F10) malignant melanoma as well as of human; (2) brain (VMM1) and lymph node (Hs 294T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Cruciferous vegetables are widely and often frequently consumed by humans (9), and a high dietary intake of these vegetables has been considered to be associated with a low risk of CRC in the involvement of epigenetic regulation (6,41). Moreover, abundant glucosinolates and their hydrolysis products, such as indoles and isothiocyanates (ITCs), are included (7,8). Allyl isothiocyanate (AITC) belongs to the ITC family and exerts several vital biological effects, including antitumor and anticancer cell proliferation effects on cultured cancer cell lines and animal tumor models (13,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cruciferous vegetables are widely and often frequently consumed by humans (9), and a high dietary intake of these vegetables has been considered to be associated with a low risk of CRC in the involvement of epigenetic regulation (6,41). Moreover, abundant glucosinolates and their hydrolysis products, such as indoles and isothiocyanates (ITCs), are included (7,8). Allyl isothiocyanate (AITC) belongs to the ITC family and exerts several vital biological effects, including antitumor and anticancer cell proliferation effects on cultured cancer cell lines and animal tumor models (13,42).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies have observed an inverse association between cancers and high dietary consumption of cruciferous vegetables, which is recognized to confer health benefits for reducing the risk of developing the disease and eliciting chemopreventive effects ( 6 ). Cruciferae is a family of vegetables, including broccoli, cabbage, cauliflower, and brussels sprouts, which are rich in isothiocyanates (ITCs), a nutraceutical agent with protection against cancer development ( 7 , 8 ). Moreover, ITCs have drawn attention owing to their capability to exert a broad spectrum of antitumor effects ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Untreated (control) cells were incubated with either 0.1% DMSO or 0.1% EtOH. The density of seeded cells was determined as previously published [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the observed side effects caused by systemic toxicity, along with drug resistance, can further contribute to the limited therapeutic efficacy against MM [ 6 , 11 , 15 ]. To this end, the development of new therapeutic approaches is of high importance in order to improve current existing protocols, thereby improving the quality of life in MM patients [ 6 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effect of AITC on lysine acetylation and methylation marks on histones H3 and H4 have been explored recently. To this end, exposure of A375 cells to 10 μM of AITC decreased HDAC and histone acetyl transferase (HAT) activities, while also affecting the acetylated and methylated content of histones (by means of assessing specific lysine modifications), suggesting that AITC can exert an epigenetically-induced anti-melanoma activity [313].…”
Section: Itcs As Anti-melanoma Agentsmentioning
confidence: 99%